Exercise retards ongoing adipose tissue fibrosis in diet-induced obese mice. Issue 3 (March 2021) - Li, Liangming; Wei, Yuan; Fang, Chunlu; Liu, Shujing; Zhou, Fu; Zhao, Ge; Li, Yaping; Luo, Yuan; Guo, Ziyi; Lin, Weiqun; Yang, Wenqi
Abstract : Exercise has been recommended as an important strategy to improve glucose metabolism in obesity. Adipose tissue fibrosis is associated with inflammation and is implicated in glucose metabolism disturbance and insulin resistance in obesity. However, the effect of exercise on the progression of adipose tissue fibrosis is still unknown. The aim of the present study was to investigate whether exercise retarded the progression of adipose tissue fibrosis and ameliorated glucose homeostasis in diet-induced obese mice. To do so, obesity and adipose tissue fibrosis in mice were induced by high-fat diet feeding for 12 weeks and the mice subsequently received high-fat diet and exercise intervention for another 12 weeks. Exercise alleviated high-fat diet-induced glucose intolerance and insulin resistance. Continued high-fat diet feeding exacerbated collagen deposition and further increased fibrosis-related gene expression in adipose tissue. Exercise attenuated or reversed these changes. Additionally, PPARγ, which has been shown to inhibit adipose tissue fibrosis, was observed to be increased following exercise. Moreover, exercise decreased the expression of HIF-1α in adipose fibrosis, and adipose tissue inflammation was inhibited. In conclusion, our data indicate that exercise attenuates and even reverses the progression of adipose tissue fibrosis, providing a plausible mechanism for its beneficial effects on glucose metabolism in obesity.